Impaired Eye-Blink Conditioning in waggler, a Mutant Mouse With Cerebellar BDNF Deficiency - Bao, Shaowen (Cold Spring Harbor Laboratory Press, 1998)
In addition to their trophic functions, neurotrophins are also implicated in synaptic modulation and learning and memory. Although gene knockout techniques have been used widely in studying the roles of neurotrophins at molecular and cellular levels, behavioral studies using neurotrophin knockouts are limited by the early-onset lethality and various sensory deficits associated with the gene knockout mice. In the present study, we found that in a spontaneous mutant mouse, waggler, the expression of brain-derived neurotrophic factor (BDNF) was selectively absent in the cerebellar granule cells. The cytoarchitecture of the waggler cerebellum appeared to be normal at the light microscope level. The mutant mice exhibited no sensory deficits to auditory stimuli or heat-induced pain. However, they were massively impaired in classic eye-blink conditioning. These results suggest that BDNF may have a role in normal cerebellar neuronal function, which, in turn, is essential for classic eye-blink conditioning.